Perancangan Desain User Interface dan User Experience Media Pembelajaran Aksara Jawa Untuk Siswa Sekolah Dasar dengan Metode Design Thinking - Januar Adi Putra; Muhammad Yusuf Auliya; Fahrobby Adnan (Bulletin of Computer Science Research, 2023)
Learning media plays a role in supporting the learning process to create variation and not boring. SDIT Bina Insani presents learning media as a means as well as a learning support. The learning media used is Javanese script card. The Javanese script card is considered sufficient to create variations in the learning experience, but it is not enough to attract students’ interest in learning and is limited to interaction with the teacher. To improve this, learning media is needed that has a user interface design and interactive user experience and able to help students make learning more fun. Design Thinking is a UI and UX design development method that focuses on extracting information and building creative ideas for solutions to encountered problems. Design thinking has five stages of the development process: Empathize, Define, Ideate, Prototype, and Test. The design of the learning media is expected to be able to provide interaction for students to understand Javanese script interactively and without being limited to learning time at school.